Computational Methods In Flip Chip Assembly. - Hj Abdul Azid, Assoc. Prof. Dr Ishak; Seetharamu, Prof. K.N.; Abdul Quadir, Assoc. Prof. Dr Ghulam (Universiti Sains Malaysia, 2002)
Flip chip technology, in the book edited by Lau (Lau, 1995) is defined as placing a chip to the substrate by flipping over the chip so that the I/O area of the chip is facing the substrate. By flipping over the chip, the interconnection between the chip and the substrate are achieved by conductive "bumps" placed directly in between the die surface and the substrate. Therefore, the whole chip surface can be utilized for active interconnections and at the same time, eliminates the need for wire bonding.